Reproductive behaviour of Malpur a and Bharat Merino ewe lambs under semi-arid condition - Maurya, V P; Naqvi, S M K; Mittal, J P (The Indian Journal of Animal Sciences, 2012)
To study reproductive behaviour and performance of Malpur a (native) and Bharat Merino (crossbred) sheep in semi-aridarea during summer, an experiment was carried out on 16 native and 16 crossbred ewe lambs which were divided inequal number of 2 groups. Animals of group 1were maintained under shed and provided a feed ration ad lib. Animalsof group 2 were sent out for grazing. Water was offered once at 16.00 hr to all animals. Incidence of estrus behaviour wasshown at an early age (393 vs 392 days) in native as compared to crossbred sheep (428 vs 451 days) in group 1 and group2 respectively. A greater proportion of native ewes ovulated (100% and 87%) subsequent to estrus behaviour as comparedto crossbred (85.7% and 66.7% ) in groups 1 and 2 respectively.